Unravelling transcriptome changes between two distinct maize inbred lines using RNA-seq - Yu-qian ZHOU; Qin-yang WANG; Hai-liang ZHAO; Dian-ming GONG; Chuan-long SUN; Xue-mei REN; Zhong-xiang LIU; Hai-jun HE; Fa-zhan QIU (Journal of Integrative Agriculture, 2018)
Seed size play a significant role in maize yield production. Two maize inbred lines with distinct seed size and weight, V671 (a large-seed inbred line) and Mc (a small-seed inbred line), were investigated by RNA-seq at 14 days after pollination (DAP), when maize endosperm undergoes an active transition from mitosis to storage accumulation. RNA-seq expression data showed that the small-seed line Mc had a higher storage accumulation activity, whereas the large-seed kernel line V671 possessed a higher DNA synthesis activity. An investigation of the pattern of increasing kernel width at serial DAPs showed that V671 experienced an increased kernel width later than did Mc, but the rate and duration of increase were longer in V671. SDS-PAGE of the storage proteins and quantitative RT-PCR of cell cycle-related genes and indole-3-acetic (IAA) synthesis genes certified that the transition from mitosis to storage accumulation starts earlier in Mc. We hypothesized that the difference in the mitosis-to-storage accumulation transition accounts for the larger seed size in V671 vs. Mc.